Allobates Femoralis como modelo para caracterizar Gradientes geográficos sutis e nítidos na bacia Amazônica - Ferreira, Anthony Santana (Instituto Nacional de Pesquisas da Amazônia - INPA, 2018)
It is well established that the occurrence of species depends on their biological needs in given environments, and that species are distributed to favorable habitat patches which are separated from each other by unsuitable habitats. However, determining how habitat heterogeneity interacts with the distribution and density of species at various geographic scales and how historical processes and the contemporary environment has influenced gene flow across landscapes remains one of the major challenges in ecology and evolutionary biology. This type of approach is still rare in Amazonia, especially when it comes to anurans. The main goals of this thesis were to investigate the role of environmental gradients on the distribution, abundance, genetic variability and gene flow of Allobates femoralis along 880 km of heterogeneous landscape in the interfluve between the Purus and Madeira rivers (PMI). In the first chapter, we tested whether soil and forest characteristics are associated with the distribution and relative abundance of A. femoralis along PMI. We show that A. femoralis is more abundant in open forests and absent or rare in dense forests and positively associated with clay-rich soils. Our findings suggest that the distribution and relative abundance of this species is shaped by gradual ecological clines. In the second chapter, we apply a multilevel modeling approach based on genomic data and circuit theory to test whether geographic distance and environmental gradients across the heterogeneous landscape of PMI influences the genetic variability and gene flow of A. femoralis. We show that spatial patterns of genetic variability and gene flow in A. femoralis are influenced by both geographic distance and environmental gradients, thus supporting the gradient hypothesis for diversification. We also identified four genetic clusters which partly paralleled phenotypic variation (femoral spot colour), strong divergence in the northeastern part of the PMI that is likely due to historical processes, and with the presence of different forest types. We suggest that investigating the role of environmental heterogeneity in other codistributed species will provide data that can be used to better understand the role of environmental gradients in the parapatric diversification of species in the Amazon.
Keywords: Allobates femoralis; Interflúvio Purus-Madeira; Heterogeneidade ambiental; Hipótese dos Gradientes; Genética de paisagens; SNPs; Amazônia